Adansonia digitata L. Stem Bark Attenuates Epileptic Seizure, Depression, and Neurodegeneration by Mediating GABA and Glutamate in Pentylenetetrazol-Kindled Rats - Adamu Muhammad; Luteino Lorna Hamman; Samaila Musa Chiroma; Martha Orendu Oche Attah; Nathan Isaac Dibal (Korean Pharmacopuncture Institute, 2023)
Objectives: Epilepsy is a neurological condition characterized by repeated seizures attributable to synchronous neuronal activity in the brain. The study evaluated the effect of acetone extract of Adansonia digitata stem bark (ASBE) on seizure score, cognition, depression, and neurodegeneration as well as the level of Gamma-Aminobutyrate acid (GABA) and glutamate in Pentylenetetrazol-kindled rats. Methods: Thirty-five rats were assigned into five groups (n = 7). Groups 1-2 received normal saline and 35 mg/kg PTZ every other day. Groups 3-4 received 125 mg/kg and 250 mg/kg ASBE orally while group 5 received 5 mg/kg diazepam daily for twenty-six days. Group 3-5 received PTZ every other day, 30 mins after ASBE and diazepam. Results: The results showed that Pentylenetetrazol (PTZ) induces seizure, reduces mobility time in force swim test and decreases the normal cell number in the brain. It also significantly decreases (p < 0.05) catalase, superoxide dismutase and reduced glutathione activities compared to the ASBE pre-treated rats. Pre-treatment with ASBE reportedly decreases seizure activities significantly (p < 0.05) and increases mobility time in the force swim test. ASBE also significantly elevate (p < 0.05) the normal cell number in the hippocampus, temporal lobe, and dentate gyrus. Conclusion: ASBE reduced seizure activity and prevented depression in PTZ-treated rats. It also prevented neurodegeneration by regulating glutamate and GABA levels in the brain as well as preventing lipid peroxidation.